Energy storage and catalytic behaviour of cmWave assisted BZT and flexible electrospun BZT fibers for energy harvesting applications - Avanish Babu Thirumalasetty; Siva Pamula; Thiyagarajan Krishnan; Vaishnavi Khade; Pathan Sharief; Siva Kumar Kota Venkata; Srinivas Adiraj; Madhuri Wuppulluri (Scientific Reports, 2024)
Abstract High-performance lead-free Barium Zirconium Titanate (BZT) based ceramics have emerged as a potential candidate for applications in energy storage, catalysis for electro chemical energy conversion and energy harvesting devices as presented in this work. In the present study hybrid microwave sintered BZT are studied for dielectric, ferroelectric and phase transition properties. BZT ceramic exhibits tetragonal structure as confirmed by the Retvield refinement studies. XPS studies confirms the elemental composition of BZT and presence of Zr. Polarization versus electric field hysteresis loops confirms the ferroelectric behaviour of BZT ceramic. Encouragingly, the BZT showed a moderate energy storage efficiency of 30.7 % and relatively good electro chemical energy conversion (HER). Excellent catalytic activity observed for BZT electrode in acid medium with low Tafel slope 77 mV dec-1. Furthermore, electrospun nanofibers made of PVDF-HFP and BZT are used to make flexible piezoelectric nano generators (PENGs). FTIR studies show that the 16 wt% BZT composite ink exhibits a higher electroactive beta phase. The optimized open-circuit voltage and short circuit current of the flexible PENG exhibits 7Vpp and 750 nA under an applied force of 3N. Thus, flexible and self-powered BZT PENGs are alternative source of energy due to its reliability, affordability and environmental-friendly nature.